Composite neuroendocrine tumor and adenocarcinoma of the rectum - Hiromi Kanno-Okada; Tomoko Mitsuhashi; Katsuhiro Mabe; Tadakazu Shimoda; Yoshihiro Matsuno (Diagnostic Pathology, 2017)
Abstract Background Although adenocarcinomas showing neuroendocrine differentiation or those mixed with high-grade neuroendocrine carcinoma (NEC) are sometimes encountered, composite tumors comprising neuroendocrine tumor (NET) Grade 1 and adenocarcinoma are exceedingly rare. Case presentation A 64-year-old male presented after testing positive for fecal occult blood at a medical check-up. A biopsy demonstrated the presence of a NET and endoscopic submucosal dissection was undertaken. Histologic examination revealed that a well differentiated tubular adenocarcinoma was present in addition to the NET. Furthermore, histological transition between the two tumors was evident. Accordingly, this case was considered to be a composite tumor comprising NET and adenocarcinoma. Conclusion Composite tumors consisting of NET Grade 1 and adenocarcinoma are exceedingly rare, and only a few examples have been reported hitherto.